UK could launch its own post-Brexit science programme in September. - O'Callaghan, Jonathan (New Scientist, 2022)
As part of the Brexit withdrawal agreement signed in December 2020, the EU agreed to allow the UK to remain part of the Horizon programme, into which the UK would pay £15 billion over seven years. THE UK will launch its own version of the European Union's €100 billion Horizon research scheme in September if a deal on continued access can't be reached, says the UK science minister, George Freeman.